2021
DOI: 10.3389/fonc.2021.699847
|View full text |Cite
|
Sign up to set email alerts
|

Gimap5 Inhibits Lung Cancer Growth by Interacting With M6PR

Abstract: ObjectiveSeveral studies have demonstrated the impacts of GTPases of immunity-associated proteins (GIMAPs) on malignant cells. However, the mechanisms through which Gimap5 regulates lung cancer cells are yet to be thoroughly investigated in the literature. Our study aimed to investigate the function of Gimap5 in the development of lung cancer.MethodsThe expression levels of the GIMAP family were analyzed in lung cancer patients of various cancer databases and lung cancer cell lines. After the survival rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The GIMAP genes encode GTP‐binding proteins, which have a unique primary structure and whose function is largely unknown. Our previous studies confirmed that Gimap5 can interact with M6PR and promote the translocation of M6PR to the cell membrane 21 . Our study showed that bronchial epithelial cells predominantly express M6PR‐CI, suggesting the importance of this receptor in epithelial cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The GIMAP genes encode GTP‐binding proteins, which have a unique primary structure and whose function is largely unknown. Our previous studies confirmed that Gimap5 can interact with M6PR and promote the translocation of M6PR to the cell membrane 21 . Our study showed that bronchial epithelial cells predominantly express M6PR‐CI, suggesting the importance of this receptor in epithelial cells.…”
Section: Discussionsupporting
confidence: 83%
“…20 We also found in a previous study that Gimap5 directly interacted with M6PR and promoted its translocation to cell membrane. 21 Therefore, we sought to explore the function of Gimap5 in response to RSV infection. Does the interaction between Gimap5 and M6PR inhibit RSV infection?…”
mentioning
confidence: 99%
“…Similarly, we detected the increase in proteins related to the immune system with anti-tumorigenic effects, such as GTPase IMAP family member 5 (GIMA5), described as a promoter of CD4+ T-cell survival and homeostasis [ 57 , 58 ]. GIMA5 also suppresses the proliferation of lung cancer cell lines [ 59 ]. In addition, we observed the increment of proteins such as mitogen-activated protein kinase 2 (MAP4K2), usually expressed in B cells of the germinal center and macrophages, which activates the c-Jun N-terminal kinases [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…TMEM176B represses adenosine triphosphate (ATP) and nigericin-induced NLRP3 in ammasome activation in dendritic cells and macrophages through ionic mechanisms. Targeting TMEM176B can emphasise anti-tumoral CD8 + T cell responses in an in ammasome-dependent manner while directly killing malignant cells 43,44 .…”
Section: Discussionmentioning
confidence: 99%